2013
DOI: 10.1002/14651858.cd008864.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen concentrate in bleeding patients

Abstract: Analysis 1.11. Comparison 1 Fibrinogen concentrate versus any comparator, Outcome 11 Thrombotic episodes (arterial and venous gra occlusion, pulmonary embolus, deep venous thrombosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 87 publications
2
79
1
7
Order By: Relevance
“…A Cochrane review reported efficacy of FC without increased thromboembolic risk [98] , though a lack of large robust trials was noted. Fibrinogen is the vital substrate of the clot and supplementation may be beneficial in the context of dilutional coagulopathy and platelet impairment [44,99] .…”
Section: Fibrinogen Concentratesmentioning
confidence: 99%
“…A Cochrane review reported efficacy of FC without increased thromboembolic risk [98] , though a lack of large robust trials was noted. Fibrinogen is the vital substrate of the clot and supplementation may be beneficial in the context of dilutional coagulopathy and platelet impairment [44,99] .…”
Section: Fibrinogen Concentratesmentioning
confidence: 99%
“…A Cochrane review evaluating the effectiveness of fibrinogen concentrate for bleeding patients found six small trials in elective surgery, all of low quality and underpowered for mortality although reporting a reduction in the incidence of allogeneic transfusions (RR 0.47, 95% CI 0.32-0.72) [62]. One trial [63] assessed the efficacy of fibrinogen concentrate therapy in bleeding patients undergoing radical cystectomy that received intra-operative fluid replacement with colloid.…”
Section: Cryoprecipitatementioning
confidence: 99%
“…A Cochrane review of predominantly cardiac surgical RCTs found that fibrinogen reduced transfusion requirements (very low-quality evidence), but there was insufficient evidence to evaluate differences in important clinical end points, including mortality. 87 …”
Section: Plateletsmentioning
confidence: 99%
“…Several small RCTs have also shown that fibrinogen administration reduces bleeding in cardiac surgery 164,165 and a Cochrane review of cardiac and non-cardiac surgery trials reported a similar finding. 87 No previous study has evaluated the predictive accuracy of low fibrinogen levels. In the COPTIC study we confirmed that this added to the discrimination of the model; however, the effect was small.…”
Section: Laboratory Reference Testsmentioning
confidence: 99%